A simple and innovative way to measure ventricular volume in a mechanical mock of the left ventricle. (March 2017) - Corazza, Ivan; Casadei, Lorenzo; Zannoli, Romano
Highlights: An "old" technique to measure elastic chamber volumes applied to a field of increasing interest. Experimental validation of this approach with traditional volume measurements obtained with an electromagnetic flowmeter. Good results: our technique proves simple, reliable and repeatable. New perspective for all users of cardiovascular biomechanical simulators. Our goal is not to demonstrate that this approach is superior to others, but simply to propose a novel reliable method. Abstract: Ongoing innovations in mechanical devices to improve the heart's performance (e.g. left ventricular assist devices, LVAD) require numerical simulations and a bench validation before animal and clinical testing of the device. One of the major requirements of mechanical mocks of the cardiovascular system is the correct evaluation of the parameters of interest (pressure, volumes, flows). This paper presents a new optical method to measure the volume changes of a generic elastic camera through videos acquisition and analysis (using Simpson integration and Matlab software). We tested our proposal with a simple syringe mock of the cardiovascular system under different conditions of simulation dynamics and varying the stroke volumes (SV). We compared our results with those obtained with a standard electromagnetic flowmeter, in terms of instantaneous volume and total SV: the curves presented the same trends (squared Pearson's coefficients greater than 0.9) with a mean difference less than 5%. The proposed optical method is simple and inexpensive and yields results comparable with those of a standard method.